BLR Size in Realistic FRADO Model: The Role of Shielding Effect - Naddaf, Mohammad-Hassan; Czerny, Bożena; Szczerba, Ryszard (Frontiers in Astronomy and Space Sciences, 2020)
Location of Broad Line Region (BLR) or inner radius of BLR in active galaxies (AGN) i.e. where the dust evaporates immediately upon departure from the accretion disk (AD) surface, scales with the source absolute luminosity. Therefore by determining this location either observationally through reverberation mapping or theoretically, one can use AGNs as an interesting laboratory to test cosmological models (Watson et al., 2011; Haas et al., 2011). In this report we focus on the theoretical side of BLR. By simulating the dynamics of matter in BLR through a realistic parametric model of AD we investigate how the Eddington ratio determines the size or in other words the radial extension and geometrical height of the BLR under different values of the model parameters.